1996
DOI: 10.1523/jneurosci.16-20-06567.1996
|View full text |Cite
|
Sign up to set email alerts
|

Properties of Convergent Thalamocortical and Intracortical Synaptic Potentials in Single Neurons of Neocortex

Abstract: We explored differences in the properties of convergent afferent inputs to single neurons in the barrel area of the neocortex. Thalamocortical slices were prepared from mature mice. Recordings were made from neurons in layer V, and either thalamocortical afferents or horizontal intracortical axons were stimulated. Monosynaptic EPSPs from both sources had latencies shorter than 1.8 msec and low shape variance. Disynaptic thalamocortical IPSPs had latencies longer than 1.8 msec. All neuronal types, as defined by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
67
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(75 citation statements)
references
References 69 publications
(88 reference statements)
8
67
0
Order By: Relevance
“…4A3). It has been suggested that latencies Ͼ1.8 ms may represent indirect, polysynaptic connections (Gil and Amitai, 1996). Thus, our latencies could mean that OH neurons fire GABA interneurons projecting to MCH cells, presumably by releasing OH peptide since the responses persisted in glutamate receptor blockers (Fig.…”
Section: Oh Cell Firing Controls Gaba Input To Mch Cells Via Oh Recepmentioning
confidence: 93%
“…4A3). It has been suggested that latencies Ͼ1.8 ms may represent indirect, polysynaptic connections (Gil and Amitai, 1996). Thus, our latencies could mean that OH neurons fire GABA interneurons projecting to MCH cells, presumably by releasing OH peptide since the responses persisted in glutamate receptor blockers (Fig.…”
Section: Oh Cell Firing Controls Gaba Input To Mch Cells Via Oh Recepmentioning
confidence: 93%
“…We also observed larger excitatory amplitudes evoked by intracortical than by either sensory or thalamocortical activation. One reason could be that sensory and thalamocortical activations recruit larger feedforward inhibition than intracortical synapses (Gil and Amitai, 1996). …”
Section: Intracortical Activationmentioning
confidence: 99%
“…Intracortical synaptic interactions in the barrel cortex are dependent, in large part, on activation of glutamatergic NMDA receptors (Gil and Amitai, 1996b;Thomson and Deuchars, 1997;Huang et al, 1998). We therefore reasoned that activation of these receptors may augment intracortical synaptic interactions and enhance the spatial spread of activity in the barrel cortex.…”
Section: Nmda Receptors Mediate Spread Of Activitymentioning
confidence: 99%